HABITAT VEGETATION OF Rafflesia arnoldii (RAFFLESIACEAE) IN PANORAMA BARU NGARAI SIANOK WEST SUMATRA (Journal of Engineering and Health Sciences, 2020)
Rafflesia is a holoparasitic plant genus that only consists of generative organs. Rafflesia has habitat conditions that vary greatly in biotic and abiotic factors. Its population decreased due to habitat destruction or natural disturbances. The objective of this study is to analyze the habitat and ecological conditions of Rafflesia arnoldii in Panorama Baru Ngarai Sianok. Purposive sampling method was used to collect the data using circular plots for Rafflesia population and vegetation. Rafflesia population data includes the  number and  phase  of development of each individual. Ecological data in the form of vegetation conditions and abiotic (physical) habitat. The Rafflesia species which found was R. arnoldii. Four populations were recorded in Ngarai Sianok consisting of 19 individuals. The identified host is Tetrastigma leucostaphylum. Vegetation within four populations was found a total of 255 individuals and 48  species  consisting  of  20  genus. Important Value  Index  (IVI)  tree vegetation is dominated by Ficus fistulosa (Moraceae) with a value of 32.37%, belta and sapling dominated by Coffea canephora (Rubiaceae) 63.53% and C. canephora (Rubiaceae)141.24%. Abiotic factors that are positively correlated was environmental humidity (RH.l), soil pH (pH) and host tree diameter (DPi).